1999
DOI: 10.1021/bp9801042
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Model for Gal4p-Mediated Expression of the Galactose/Melibiose Regulon in Saccharomyces cerevisiae

Abstract: A mathematical model based on equilibrium binding between Gal4p and its specific DNA binding site has been developed. A model for GAL gene expression solely due to cooperativity, as a function of Gal4p concentration, has been developed for a gal80 mutant. The above model was extended to include other known regulatory molecules, namely Gal80p and Gal3p. Parameters determined from the above simulation were then used to represent a physiological status of gene expression in response to glucose (in terms of Gal4p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Previous modeling work had predicted that the switch response of the network would be unaffected if Gal80p and Gal3p were not autoregulated (16). The results from these studies indicate that at equal levels of the activator and repressor proteins expressed from the tetO 2 promoter under nonrepressing conditions, the galactose network is not inducible.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous modeling work had predicted that the switch response of the network would be unaffected if Gal80p and Gal3p were not autoregulated (16). The results from these studies indicate that at equal levels of the activator and repressor proteins expressed from the tetO 2 promoter under nonrepressing conditions, the galactose network is not inducible.…”
Section: Discussionmentioning
confidence: 74%
“…Modeling has also indicated that the switch is only functional if Gal80p and Gal3p are subject to the same regulation (6). Prior work has demonstrated that the response properties of the system are highly sensitive to relative levels of Gal4p, Gal80p, and Gal3p (16). The Gal2p galactose permease promoter region contains two UASs, whereas the promoter regions for Gal80p and Gal3p contain one UAS.…”
mentioning
confidence: 99%
“…Both the ternary and non -ternary scenarios have been previously modelled [35,75] by considering their behaviour at equilibrium. Our model assumes the indirect and nonternary hypothesis , although we do not model the transport of gal80p between the cytoplasm and nucleus.…”
Section: Direct or Indirect Induction?mentioning
confidence: 99%
“…Quantification of gene regulatory network is essential for the optimization and operation of bioreactors for the production of foreign proteins. Some of the well‐known examples of genetic regulatory systems that have been explained in quantitative terms are lac operon [13], bacteriophage λ [14], the trp repressor [15] and GLU‐GAL system in yeast [16]. The quantification is typically done by assuming equilibrium between protein–DNA and protein–protein interactions.…”
Section: Introductionmentioning
confidence: 99%